Role of Urokinase-Type Plasminogen Activator Receptor in the Regulation of Angiogenic Properties of Sca1+ Vasculogenic Progenitor Cells - К. V. Dergilev; Z. I. Tsokolaeva; I. B. Beloglazova; Yu. D. Vasilets; D. O. Traktuev; N. B. Kulbitsky; E. V. Parfenova (Общая реаниматология)
Neoangiogenesis is the key process determining myocardial regeneration after infarction. The urokinase-type plasminogen activator receptor (uPAR) is known to play an important role in the regulation of endothelial cell function and postnatal angiogenesis. However, uPAR its involvement in the regulation of the properties of vascular progenitor cells remains poorly studied.   Aim: to evaluate uPAR expression on the surface of resident cardiac vascular progenitor cells (rcVPCs) and its impact on angiogenic cell properties in vitro as well as postinfarction cardiac vascularization.   Materials and Methods. We used immunofluorescent analysis of cryosections of a murine myocardial infarction model to characterize vessels and rcVPCs, and evaluatedв the angiogenic properties potential of vasculogenic progenitor cells using the «tube assay» and induction ofinducing differentiation in a specialized medium.   Results. We have found that the majority of Sca-1+ rcVPCs express the urokinase receptor and endothelial cell markers on their surface and are capable of proliferation and integration into the newly formed vessels in the injured area, indicating their possible involvement in thecontribution to vascularization process after infarction. After acute ischemic injury, the accumulation of vasculogenic progenitor cells (8+2 and 27+7 cells per visual field, respectively; P = 0.032) and vascularization processes (85+11 and 166+25 capillaries per visual field, respectively; P = 0.033) were observed in myocardium of uPAR-/- animals, compared with wild-type animals. Our studies demonstrated that Sca-1+ rcVCPs derived from uPAR-/- murine hearts demonstrated a reduced ability to form capillary-like structures and endothelial differentiation compared with Sca-1+ rcVCPs from hearts of wild-type mice.   Conclusion. Thus, uPAR deficiency may lead to impaired vasculogenic properties of Sca-1+ rcVCPs, which is likely due to the loss of regulatory influence of specific ligands and the ability to interact with signaling mediators such as integrins. From the viewpoint of regenerative medicine, the modulation of uPAR activity can be considered as a potential targetpromising approach for targeted regulation of vasculogenic progenitor cells properties and postnatal angiogenesis.Highlight   The urokinase-type plasminogen activator receptor is involved in the regulation of the angiogenic properties of Sca1+ vasculogenic progenitor cells.